SROI sebagai Alat Evaluasi: Meningkatkan Akuntabilitas dalam Pengabdian Masyarakat - Budi Lesmana; Sakti Muda Nasution; Mira Ismirani Fudsy (LPPM POLITEKNIK LP3I BANDUNG, 2026)
Social Return on Investment (SROI) has emerged as a significant evaluation tool for enhancing accountability in community service programs. This article explores how the application of SROI can provide a more transparent and measurable framework for assessing the social, economic, and environmental impacts of community engagement initiatives. Aiming to understand the ways in which SROI can be integrated into evaluation practices, this research employs a qualitative approach, including case studies of several community service programs that have implemented SROI. The findings indicate that SROI not only aids in measuring the social value added by these programs but also increases stakeholder trust and facilitates ongoing monitoring of the impacts generated. Thus, this article concludes that SROI can serve as a vital instrument in efforts to strengthen accountability and transparency in community service initiatives, while also encouraging greater investment in programs that deliver tangible benefits to communities.